Rumah Tua: Local Wisdom and Community Perspective of Ouw People in Saparua Island, Maluku - Elsina Titaley; Christwyn Ruusniel Alfons (Smart Society, 2025)
In Maluku, traditional houses are not only physical structures but also carry symbolic values that preserve kinship and communal ties. This research aims to analyze how the Ouw community perceives the physical construction of Rumah Tua in relation to the cultural value of brotherhood. The study employed a qualitative descriptive approach with ten key informants, including traditional leaders, descendants residing in Rumah Tua, and community members who have migrated. Data were collected through in-depth interviews and observations, and analyzed using Miles and Huberman’s interactive model. Findings reveal that Rumah Tua embodies both sacred and social values that connect generations, whether living locally or abroad. It functions as a cultural symbol of identity (mataruma), a space for transmitting values of solidarity and cooperation, and a unifying point for descendants despite migration and modernization. The practice of maintaining, visiting, and renovating these houses demonstrates the persistence of emotional and cultural attachment across generations. This study highlights the significance of Rumah Tua as a form of social capital that sustains cultural identity and brotherhood within indigenous Maluku communities, offering insights for cultural preservation and community empowerment.